The Correlation Between Probiotics and Gastroesophageal Reflux Disease (GERD): A Comprehensive Review - Hendrik; Suryadi (International Medical Journal Corp. Ltd, 2024)
Background: It has been demonstrated that probiotics, or live microorganisms, can lessen GERD symptoms and enhance gut health. They can help with bowel movements and abdominal pain, which helps with managing GI tract disorders in general and irritable bowel syndrome in particular (IBS). Methods: We conducted a search without sample size restrictions in the PubMed and Web of Science databases to find prospective studies on dyspepsia, heartburn, regurgitation, and GERD. The analysis comprised a total of ten published prospective studies. Result: Studies have reported that probiotics can alleviate GERD symptoms, including reflux. These studies have shown that probiotics can reduce regurgitation, improve reflux or heartburn, alleviate dyspepsia, and improve other upper gastrointestinal symptoms like nausea, abdominal pain, and gas-related symptoms. Conclusion: In the general adult population, probiotics have been shown to lessen upper gastrointestinal symptoms of GERD, especially those derived from Lactobacillus and Bifidobacterium. By interacting with stomach mucosal receptors, they modify the immune response and antagonistic activity towards potential pathogens, accelerating gastric emptying.